2x+7-9x=9-(7x+2)

Simple and best practice solution for 2x+7-9x=9-(7x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7-9x=9-(7x+2) equation:


Simplifying
2x + 7 + -9x = 9 + -1(7x + 2)

Reorder the terms:
7 + 2x + -9x = 9 + -1(7x + 2)

Combine like terms: 2x + -9x = -7x
7 + -7x = 9 + -1(7x + 2)

Reorder the terms:
7 + -7x = 9 + -1(2 + 7x)
7 + -7x = 9 + (2 * -1 + 7x * -1)
7 + -7x = 9 + (-2 + -7x)

Combine like terms: 9 + -2 = 7
7 + -7x = 7 + -7x

Add '-7' to each side of the equation.
7 + -7 + -7x = 7 + -7 + -7x

Combine like terms: 7 + -7 = 0
0 + -7x = 7 + -7 + -7x
-7x = 7 + -7 + -7x

Combine like terms: 7 + -7 = 0
-7x = 0 + -7x
-7x = -7x

Add '7x' to each side of the equation.
-7x + 7x = -7x + 7x

Combine like terms: -7x + 7x = 0
0 = -7x + 7x

Combine like terms: -7x + 7x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 0.1x=0.3 | | 8=2r | | -5x-9=12-4 | | 9x+1+5x+11=180 | | 1.4x=-28 | | -3+w=7 | | (x+3)+(x+3)=88 | | 16=4(x-2)-(x-9) | | 1x-31=8 | | (n-11)(3n+7)=0 | | 2x=(x+4)+5 | | x+(x-2)+9=29 | | 5+v=2 | | 12983+z=21137 | | -8+u=5 | | 15x-299=5x-9 | | g=r+wx | | 918.2+v=1920.8 | | -6-y=-3 | | 106-6x=12x+24 | | 1x+17=3x-3 | | 12a^2+7a-12= | | (44)(1)=(3a) | | 912+e=1201 | | 9m-6+3m=60 | | 3.4=-13.6-3.4c+1.7c | | P+12982=25000 | | 2(3d+7)=5+6b | | 2(6h+1)=4(h-5)-2 | | 5x-1+4=-7 | | J+1239=1300 | | 4y-8+y+48=6y+40-4y |

Equations solver categories